The Influence Of Religiosity And Ease Of Use Of Information Technology On The Decision To Pay Zakat, Infak, And Sedah (Zis) At The National Zakat Amil Agency (Baznas) Of Pekanbaru City - Azizul Fikri; Zulkifli; Mahyarni (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of religiosity and ease of use of information technology on the decision to pay zakat, infaq, and alms (ZIS) at the National Zakat Agency (BAZNAS) of Pekanbaru City. The study uses a quantitative approach with a causal method. The study population is all muzakki who pay ZIS through BAZNAS Pekanbaru City, totaling 1,081 people, with a sample of 100 respondents determined using a purposive sampling technique. Data collection was carried out through a questionnaire with a five-level Likert scale. Data analysis used multiple linear regression analysis with the help of the SPSS program version 27.00, which was preceded by validity, reliability, and classical assumption tests. The results of the study indicate that religiosity partially has a positive and significant effect on the decision to pay ZIS, as evidenced by the calculated t value being greater than the t table at a significance level of 5 percent. Ease of use of information technology is also proven to have a positive and significant effect on the decision to pay ZIS. Simultaneously, religiosity and ease of use of information technology significantly influenced the decision to pay ZIS, with a coefficient of determination of 89.9 percent, while the remainder was influenced by other variables outside the research model. These findings indicate that the decision to pay ZIS is the result of the interaction between spiritual motivation, reflected in religiosity, and information technology support that facilitates the payment process. This research is expected to provide consideration for BAZNAS (National Agency for Zakat and National Agency for Zakat Management) in improving its ZIS collection strategy by strengthening religiosity and optimizing digital services.